2022
DOI: 10.1128/jvi.02193-21
|View full text |Cite
|
Sign up to set email alerts
|

ARF1 with Sec7 Domain-Dependent GBF1 Activates Coatomer Protein I To Support Classical Swine Fever Virus Entry

Abstract: Classical swine fever virus (CSFV), a positive-sense, enveloped RNA virus that belongs to the Flaviviridae family, hijacks cell host proteins for its own replication. We previously demonstrated that Golgi-specific brefeldin A-resistance factor 1 (GBF1), a regulator of intracellular transport, mediates CSFV infection. However, the molecular mechanism by which this protein regulates CSFV proliferation remains unelucidated. In this study, we constructed a series of plasmids expressing GBF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…COP I and ARF1 form a complex with Golgi-specific brefeldin A resistance factor 1 (GBF1) [ 152 ]. Zhang et al first demonstrated that the GBF1–ARF1–COP I axis mediates CSFV transportation from early to late endosomes, promoting viral entry into swine umbilical vein endothelial cells (SUVECs) [ 153 ]. GBF1 was previously validated as being important in CSFV replication in SUVECs [ 154 ].…”
Section: Intracellular Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…COP I and ARF1 form a complex with Golgi-specific brefeldin A resistance factor 1 (GBF1) [ 152 ]. Zhang et al first demonstrated that the GBF1–ARF1–COP I axis mediates CSFV transportation from early to late endosomes, promoting viral entry into swine umbilical vein endothelial cells (SUVECs) [ 153 ]. GBF1 was previously validated as being important in CSFV replication in SUVECs [ 154 ].…”
Section: Intracellular Traffickingmentioning
confidence: 99%
“…Meanwhile, CSFV infection promoted GBF1, ARF, and COP I mRNA expression. These results indicate that CSFV infection induces the expression of the GBF1–ARF–COP I complex and mediates the distribution of COP I-coated vesicles [ 153 ].…”
Section: Intracellular Traffickingmentioning
confidence: 99%
“…ARF1 can recruit soluble cytosolic effectors to the membranes, such as coat protein complex I coatomer, clathrin cargo adaptors, and lipid metabolism enzymes, to regulate the vesicular assembly or remodel the membranes [63][64][65][66] . Previous work has shown that ARF1 might be involved in multiple virus infections with unknown or several proposed mechanisms [31][32][33][34][35][67][68][69][70][71] , while whether and how ARF1 has a role in SARS-CoV-2 infection were unknown before our study. Particularly, Faure et al have reported that the HIV-I Nef protein can interact with both cluster of differentiation 4 (CD4) and ARF1, and hijack ARF1 onto the endosomal membranes to downregulate CD4 by accelerated endocytosis and lysosomal degradation 31 .…”
Section: Discussionmentioning
confidence: 86%
“…Studies have shown that cellular cholesterol is essential for CSFV infection, and cholesterol depletion significantly blocks virus internalization and thus inhibits CSFV infection at the initial stage [ 39 ]. Moreover, inhibiting coatomer protein I (COP I) function and Niemann-pick C1 (NPC1) expression, which impairs cholesterol transport and leads to cholesterol and virion accumulation in early endosomes, thus suppresses CSFV invasion and replication [ 40 , 41 ]. To our knowledge, our study is the first detailed report on alterations to intracellular cholesterol in PK-15 cells during CSFV infection.…”
Section: Discussionmentioning
confidence: 99%